Insulin resistance in obese children and adolescents: from mechanisms to screening and exercise intervention - Cao, Youxiang; Xu, Rui; Zhang, Jie (Frontiers in Pediatrics, 2026)
The early onset of obesity has become a serious public health problem and is accompanied by the low age range of various metabolic diseases. Obesity is strongly associated with the development of Insulin resistance (IR). IR is considered the pathological basis of several metabolic diseases and is associated with a high likelihood of future chronic disease in adulthood. But the onset of IR is highly insidious, and the early development of a predictive model of morbidity is essential to the prevention. Exercise can effectively prevent IR, but the optimal intensity and dose of exercise are controversial. Thus, this narrative review shows the mechanisms, screening, and exercise interventions of IR in obese children and adolescents.